Tensorial Model for Photolithography Aerial Image Simulation. (19th October 2009) - Fossati, Caroline; Bourennane, Salah; Sabatier, Romuald; Di Giacomo, Antonio
Abstract : In this paper, we propose to adapt the multilinear algebra tools to the tensor of Transmission Cross-Coefficients (TCC) values for aerial image simulation in order to keep the data tensor as a whole entity. This new approach implicitly extends the singular value decomposition (SVD) to tensors, that is, Higher Order SVD or TUCKER3 tensor decomposition which is used to obtain lower rank-( K 1,   K 2,   K 3,   K 4 ) tensor approximation (LRTA( K 1,   K 2,   K 3,   K 4 ) ). This model requires an Alternating Least Square (ALS) process known as TUCKALS3 algorithm. The needed number of kernels is estimated using two adapted criteria, well known in signal processing and information theory. For runtime improvement, we use the fixed point algorithm to calculate only the needed eigenvectors. This new approach leads to a fast and accurate algorithm to compute aerial images.